Aglutininas antileptospíricas em búfalos do Vale do Ribeira, Estado de São Paulo - Langoni, Hélio [UNESP]; Del Fava, Claudia; Cabral, Kenio De Gouvêa; Silva, Aristeu Vieira Da; Chagas, Sérgio Aguiar Pacheco (Universidade Federal de Santa Maria, 1999)
A total of 403 buffaloes serum samples from seven counties of Vale do Ribeira, São Paulo State, Brazil, obtained between January 1992 and June 1993, were studied to determine the prevalence of anti-leptospire agglutinins using the microscopic serum agglutination test. A titre of 100 and above was considered positive. The highest titre found was 1600 to the sorovar bratislava (one sample), followed by 800 to wolffi (4 samples). 152 (37.7%) samples from the total were positive to the serovars tested, and their prevalence, in decreasing order, was: wolffi (68, 44.8%), icterohaemorrhagiae (51, 33.6%), hardjo (51, 33.6%), castellonis (25, 16.5%), djasiman (12, 7.9%), grippotyphosa (10, 6.6%), pomona (8, 5.2%), bratislava (6, 4.0%), copenhageni (5, 3.3%) and tarassovi (4, 2.7%).

Foram estudadas aglutininas antileptospíricas em 403 amostras de soro de búfalos, provenientes de sete Municípios do Vale do Ribeira, Estado de São Paulo, coletadas no período de janeiro de 1992 a junho de 1993. Utilizou-se o teste de soroaglutinação microscópica, considerando-se positivas as amostras cujo título fosse igual ou superior a 100. O maior título encontrado foi 1600 para o sorovar bratislava (1 amostra), seguido de 800 para wolffi (4 amostras). Do total, 152 (37,7%) das amostras foram positivas, sendo que, dentre os sorovares testados, a prevalência em ordem decrescente foi: wolffi (68, 44,8%), icterohaemorrhagiae (51, 33,6%), hardjo (51, 33,6%), castellonis (25, 16,5%), djasiman (12, 7,9%), grippotyphosa (10, 6,6%), pomona (8, 5,2%), bratislava (6, 4,0%), copenhageni (5, 3,3%) e tarassovi (4, 2,7%).
Anti-leptospire agglutinins in buffaloes from Vale do Ribeira, São Paulo State, Brazil
Keywords: leptospira; microscopic serum agglutination; buffaloes; leptospira; soroaglutinação microscópica; búfalos